RAGAM HIAS MAKAM SYECH BURHANUDDIN ULAKAN KECAMATAN ULAKAN TAPAKIS KABUPATEN PADANG PARIAMAN DALAM KAJIAN ESTETIKA VISUAL - Wahyu Mulia; Ahmad Akmal; Harrisman Harrisman (Institut Seni Indonesia Padang Panjang, 2016)
ABSTRACT This article aims at revealing the visual aesthetic meaning of Syech Burhanuddin’s tomb decoration in Ulakan Pariaman. Syech Burhanuddin’s tomb is cultural artifact that becomes the historical evidence for the development of Islam in Minangkabau in the 17th century particularly in Ulakan. The motifs of decoration are inspired from nature namely the shape of plant distilled in the forms of leaf, rod/stem, flower bud and flower on the building of tomb block. The application of decoration motifs can be found on building parts such as on the tower peak, singok, building pole, bubungan and tomb’s wall that can give aesthetic value, beauty, and grandeur to that building. The tomb’s religious value and sanctity can be seen and sensed by people who come to do pilgrimage to the tomb of Syech Burhanuddin in Ulakan. This research is conducted by using qualitative approach because it is in accordance with its study that has descriptive characteristic. Keywords: decoration, Syech Burhanuddin’s tomb, visual aesthetics